2021
DOI: 10.1177/21676968211000498
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting Versus Autonomy Supportive Parenting? A Latent Class Analysis of Parenting Among Emerging Adults and Their Psychological and Relational Well-Being

Abstract: We aim to identify typologies of parenting among emerging adults and describe how parenting typologies are related to their life satisfaction, self-efficacy, and parent-child relationship. Using a three-step latent class approach, we analyzed 472 mother-child and 426 father-child relations. We recruited the students from a private university in Upstate New York. We confirmed four parenting classes among emerging adult mothers and fathers: helicopter parenting, autonomy supportive parenting, uninvolved parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Some research results have shown that there are emerging adults who view helicopter parents as emotionally supportive and express satisfaction with their lives (Fingerman et al, 2012 ;Padilla-Walker & Nelson, 2012). However, most of the studies have focused on the decreasing well-being of emerging adults of helicopter parenting (Hwang & Jung, 2022;Schiffrin et al, 2019;Yam & Kumcagiz, 2021) and life satisfaction (Gençdoğan & Gülbahçe, 2021;Schiffrin. et al, 2014;Yam & Kumcagiz, 2021) revealed that they are related.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some research results have shown that there are emerging adults who view helicopter parents as emotionally supportive and express satisfaction with their lives (Fingerman et al, 2012 ;Padilla-Walker & Nelson, 2012). However, most of the studies have focused on the decreasing well-being of emerging adults of helicopter parenting (Hwang & Jung, 2022;Schiffrin et al, 2019;Yam & Kumcagiz, 2021) and life satisfaction (Gençdoğan & Gülbahçe, 2021;Schiffrin. et al, 2014;Yam & Kumcagiz, 2021) revealed that they are related.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To estimate latent classes of intergenerational solidarity, we dichotomized all solidarity variables for the following reasons. First, previous studies have suggested that categorical indicators create better class separation in interpretation than do ordinal or continuous indicators (Hwang & Jung, 2021; Vasilenko, 2021). Second, when ordinal variables are strongly skewed (e.g., associational and functional solidarity), dichotomous transformations are likely to provide better specification of parameter estimates (DeCoster et al, 2009; Macia & Wickham, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…They show that students with parents who offered the lowest autonomy to children with a moderate level of control had higher levels of mathematics achievement than their peers had. Hwang and Jung (2021) used an identical analytic approach and identified four patterns of parenting combining different levels of helicopter parenting and autonomy supportive parenting among emerging adults. Emerging adults belonging to the pattern combining low helicopter parenting/high autonomy supportive reported higher self-efficacy and parent-child relationship than those belonging to the other patterns.…”
Section: Conditional Parenting Supportmentioning
confidence: 99%
“…Although other studies used as we did the paradigm of support for autonomy/psychological controlling practices to cluster parenting profiles, the parenting dimensions considered were usually different. They sometimes focus on the communication in the family (Romm & Metzger, 2021), emotional warmth, monitoring of child and reaction in face of child' anxiety (Beato et al, 2016), or authoritative and authoritarian parenting styles (McKinney et al, 2018), etc. In other studies participants were emerging adults, thus much older than are our participants (Howard et al, 2020;Hwang & Jung, 2021;McKinney et al, 2018), and participants' perceptions of their father and mother were combined to define profiles. Finally, parental control, the display of love, care and warmth embody different meanings and they are performed differently in the cultural contexts of Western countries and those of East Asian countries (Shi & Tan, 2020).…”
Section: Parenting Profilesmentioning
confidence: 99%